Transformasi Limbah Lingkungan Menjadi Kerajinan Tangan pada Siswa Sekolah Dasar di Desa Cupak, Kecamatan Ngusikan, Kabupaten Jombang - Shobirin, Mochammad Syafiuddin; Zakki, Mohammad; Fatih, Muhammad Al; Fakhrunnajah, Muhammad Ekky; zairi, zairi (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2024)
This research aims to overcome the problem of plastic waste in the school environment through training in making handicrafts from inorganic waste. In training conducted at SDN Cupak, Ngusikan District, Jombang Regency, students in grades 3, 4 and 5 were taught to process used straws into creative craft products. This activity involves preparation stages, educational implementation, and direct practice with the aim of improving students' skills and environmental awareness. The results achieved include mastery of craft techniques, increased creativity and product quality, as well as positive impacts on education and society. This activity is expected to encourage students to play an active role in waste management and increase enthusiasm for learning. Socialization develops skills and creativity, which increases public awareness that recycled waste can be turned into artistic crafts. Assistance activities are carried out by changing inorganic waste such as plastic straws into brooches, flowers, toys, and so on. As a result of this program, people improve their waste handling and waste management skills, allowing them to be creative with waste by turning paper and plastic waste into value-added work.